HUKUM ISLAM DAN BUDAYA LOKAL DI MASYARAKAT MUSLIM PATTANI THAILAND (Integrasi, Konflik dan Dinamikanya) - ali sodiqin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2016)
The presence of Thai people in Pattani through annexation or conquest, from the Kingdom of Siam to Thailand have changed the socio-cultural Muslim community. Thai Buddhist nation perform a lot of cultural assimilation of Malay Muslim Pattani. The assimilation pursued through politics, education, culture, and law. Political stripes do with the ideology developed, namely